2016
DOI: 10.1186/s12939-016-0369-x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting “back home” and “here”: how Northeast African migrant women perceive and experience health during pregnancy and postpartum in Canada

Abstract: BackgroundInternational migration and the number of migrant women who experience pregnancy and childbirth in receiving countries have significantly increased in the last two decades. Migrant women often have unmet social and economic needs during pregnancy, and are more likely to have problems unaddressed by health care systems. In this qualitative study, we explored migrant women’s perceptions and experiences of health during pregnancy and postpartum, while participating in a perinatal program offered through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 30 publications
(47 reference statements)
0
38
0
4
Order By: Relevance
“…Similar to other studies, the work of CLWs in trauma-informed capacity-building initiatives is facilitated by their shared identity and ethnicity [1,18,36], shared refugee experience [5,11,21] and skills [5,34,37]. CLWs in this study engaged in many similar approaches to the work of Liaison Workers reported in the literature, including strategies to improve the cultural appropriateness of services [15,17,38], the use of peer review and support [39,40], emphasis on the development of trusting relationships between refugees and service providers [8,18,41], adopting a holistic needs-based approach [39,42,43] and developing various group programs in order to address the needs of the community [3,38]. Consistent with a trauma-informed approach, CLWs in this study expressed that their work is fundamentally based on the principle of empowerment, as demonstrated by their initiatives as community leaders to develop projects that build on their community's strengths in order to achieve particular goals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies, the work of CLWs in trauma-informed capacity-building initiatives is facilitated by their shared identity and ethnicity [1,18,36], shared refugee experience [5,11,21] and skills [5,34,37]. CLWs in this study engaged in many similar approaches to the work of Liaison Workers reported in the literature, including strategies to improve the cultural appropriateness of services [15,17,38], the use of peer review and support [39,40], emphasis on the development of trusting relationships between refugees and service providers [8,18,41], adopting a holistic needs-based approach [39,42,43] and developing various group programs in order to address the needs of the community [3,38]. Consistent with a trauma-informed approach, CLWs in this study expressed that their work is fundamentally based on the principle of empowerment, as demonstrated by their initiatives as community leaders to develop projects that build on their community's strengths in order to achieve particular goals.…”
Section: Discussionmentioning
confidence: 99%
“…Ve zkoumaných studiích, které tak činí, je migrace vymezena základním pohybem směřujícím k překročení národních hranic [Essén 2001;Quintanilha et al 2016;Urquia et al 2010a] a je charakterizována jako tranzice [Callister, Birkhead 2002;Collins, Zimmerman, Howard 2011;Zeitlin et al 2004]. Popřípadě ji výzkumníci rozlišují podle příčin a motivací [Adanu, Johnson 2009;Balaam et al 2013;Janevic, Savitz, Janevic 2011].…”
Section: Migrace Jako Tranziceunclassified
“…Celá řada studií [např. Balaam et al 2013;Mcleish 2005;Hoban, liamputtong 2013;Quintanilha et al 2016;Merry et al 2013;McGlade, Saha, Dahlstrom 2004] ukazuje, že migrantky postrádají podporu širší rodiny a cítí se být v důsledku migrace izolovány [Bollini, Stotzer, Wanner 2007].…”
Section: Neformální Typ Péčeunclassified
See 2 more Smart Citations